The first step is to simplify the expression on either side of the equation:
x + 3 = 12.
Now, we solve as we did earlier:
Solve the equation z - 6 = 5.
If we write
z = 5,
we've made the quantity on the left heavier by 6 but haven't made the quantity on the right heavier at all. Uh-oh—the scale's a-tippin'. To correctly solve the equation, we need to change each quantity by the same amount. We add 6 to the expression z - 6 and also add 6 to the expression 5 to get
z = 11
Solve the equation 9 - 8 + 2 = x + 4.
First, simplify the expression on each side of the equation to find that